Vitamin D deficiency in patients with diabetes and its correlation with water fluoride levels. (23rd December 2022) - Kumar, Pramod; Gupta, Rasna; Gupta, Ankit
Abstract: Chronic exposure to fluoride through drinking water has been linked to insulin resistance and resulting type 2 diabetes mellitus (T2DM). Here, we aim to study the impact of water fluoride levels on blood glucose and vitamin D levels. A hospital-based study was conducted on diabetic patients ( n = 303) at All India Institute of Medical Sciences (AIIMS), Raebareli outstation patient department (OPD). The relationship between vitamin D or fasting blood glucose levels (BGLs) with water fluoride levels was estimated through Spearman's rank correlation. We found a significant negative correlation between water fluoride and vitamin D levels [ rs = −0.777, p -value < 0.001] and a positive correlation between water fluoride and fasting BGLs [ rs = 0.178, p -value <0.05]. The participants residing in fluoride-endemic areas ( F > 1.5 mg/L) had higher odds of severe vitamin D deficiency (odds ratio: 5.07, 95% CI: 1.9–13.2, p -value = 0.0009). The results demonstrate that vitamin D deficiency and fasting BGLs are significantly associated with water fluoride levels. This study signifies the role of fluoride toxicity in poor glycemic control and derived vitamin D deficiency. Vitamin D supplementation and the application of standard household water purification devices are recommended to tackle vitamin D deficiency in fluoride-endemic areas. HIGHLIGHTS: Water fluoride levels had a negative correlation with vitamin D deficiency and a positive correlation with blood glucose levels. Toxic levels of fluoride in drinking water appeared as a risk factor for developing vitamin D deficiency. Severe vitamin D deficiency and high blood glucose levels were observed in patients from fluoride-endemic areas compared to non-endemic areas. Graphical Abstract